2022
DOI: 10.3390/nu14235079
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of a Multinutrient Supplement on Cognition, Mood and Biochemical Markers in Middle-Aged Adults with ‘Optimal’ and ‘Sub-Optimal’ Diets: A Randomized Double Blind Placebo Controlled Trial

Abstract: Background: Previous randomized controlled trials examining cognitive and mood effects of combination multivitamin supplements in healthy, non-clinical adults have reported mixed results. One purported explanation for this is that the dietary status of participants at the start of supplement interventions may influence the magnitude of the effect of supplementation. Methods: In this study, we evaluated the effect of a multinutrient formula containing B group vitamins, Bacopa monniera and Ginkgo biloba on memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Even in the MAST population, only two participants achieved a MeDi score ≥ 10. This is despite the trial’s intentional recruitment strategy, aiming for diversity in diet quality by including 50 % of the population adhering to an ‘optimal’ diet and the other 50 % to a sub-optimal diet scored through the Diet Screening Tool ( 25 ) . While there were still only two participants in this trial with a MeDi score ≥ 10, geographical variations might also contribute to the observed low adherence, particularly given the documented low adherence to vegetables in Australian populations ( 52 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the MAST population, only two participants achieved a MeDi score ≥ 10. This is despite the trial’s intentional recruitment strategy, aiming for diversity in diet quality by including 50 % of the population adhering to an ‘optimal’ diet and the other 50 % to a sub-optimal diet scored through the Diet Screening Tool ( 25 ) . While there were still only two participants in this trial with a MeDi score ≥ 10, geographical variations might also contribute to the observed low adherence, particularly given the documented low adherence to vegetables in Australian populations ( 52 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The three clinical trials included comprised the Memory and Attention Supplement Trial (MAST) NCT03482063 ( 25 ) , the Phospholipid Intervention for Cognitive Ageing Reversal (PLICAR) trial ACTRN12613000347763 ( 26 ) and the Cognitive Ageing Nutrition and Neurogenesis (CANN) trial NCT02525198 ( 27 , 28 ) . The MAST trial evaluated the impact of a 12-week intervention of vitamin B and herbal supplementation on cognition and mood in healthy middle-aged adults, while the PLICAR trial explored the neurocognitive effects of a 6-month supplementation with a phospholipid-rich milk protein (Lacprodan® PL-20, Arla Foods Ingredients, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…The Australian modification of the DST [ 26 , 27 ] was used, requiring only minimal adaptation to the New Zealand context (e.g., updating the name of popular fast food restaurants). The DST comprises 20 items, with 18 items related to the frequency of consumption of particular foods (e.g., “How often do you usually eat wholegrain breads or crackers?”) and 2 items related to the number of servings consumed (e.g., “How many different vegetable servings do you usually have at your main meal of the day?”).…”
Section: Methodsmentioning
confidence: 99%
“…A change score (post-MTF − pre-MTF) was calculated to measure the subjective change in mood in response to the cognitive stressor. The questionnaire set has previously been used to measures stress reactivity in response to cognitive demand [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cognition was assessed using the SUCCAB [39], a battery of eight computerized cognitive tasks including simple reaction time (SRT), choice reaction time (CRT), immediate (IRM) and delayed recognition memory (DRM), congruent (CS) and incongruent stroop (ICS), spatial working memory (SWM), and contextual recognition memory (CRM). Performance on these tasks has been shown to negatively correlate with age [39], and be modified by nutritional interventions [40,41]. The following is a brief description of each SUC-CAB task.…”
Section: Swinburne University Computerized Cognitive Assessment Batte...mentioning
confidence: 99%